Comparing a new hydroexpression technique with conventional forceps method for SMILE lenticule removal. Issue 8 (9th November 2017) - Ng, Alex L K; Cheng, George P M; Woo, Victor C P; Jhanji, Vishal; Chan, Tommy C Y
Abstract : Background: We described a modified 'hydroexpression' technique for the lenticule removal during small-incision lenticule extraction (SMILE) surgery and compared the results with conventional forceps method. Methods: This was a retrospective, comparative study of 50 patients who underwent SMILE surgery by the same surgeon. We compared the 1-week and 3-months postoperative results after SMILE using the hydroexpression technique with the conventional forceps technique. Main outcome measures included uncorrected distance visual acuity, corrected distance visual acuity, refractive accuracy, safety index and efficacy index. Results: The baseline characteristics were comparable between both groups. At postoperative 1 week, the safety index in forceps and hydroexpression group was 0.93±0.11 and 0.97±0.10, respectively (P=0.246). At 3 months, they were 1.00±0.06 and 0.99±0.09 (P=0.850). For efficacy indices, at 1 week they were 0.84±0.17 and 0.91±0.17 (P=0.158). At 3 months, they were 0.92±0.13 and 0.94±0.19 (P=0.624). All eyes aimed for a plano target. 96% in forceps group and 90% in hydroexpression group were within ±0.50 dioptre (D) in spherical equivalent refraction (SEQ) correction at postoperative 3 months (P=0.567). The mean errors of SEQ correction were −0.10±0.21 D in forceps group and −0.08±0.30 D in hydroexpression group (P=0.705). Conclusion: Hydroexpression was simple and safe and had early results comparable to the conventional forceps technique. This technique was particularly useful for cases with more adhesions between lenticule and anterior cap, thin lenticule cases and for the inexperienced SMILE surgeons.